Low-density large-size polyimide foam material and preparation method thereof
The preparation of low-density large-size polyimide foam materials by one-step method has solved the problems of high-density and large-size cracking in the prior art, and achieved the low-density, low thermal conductivity and excellent flame retardant properties of the material, uniform pore size and stable performance.
Patent Information
- Application Number
- CN202411566841.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-21
AI Technical Summary
It is difficult to produce low-density and large-size polyimide foam materials in the prior art, and the problems of high-density and large-size cracking in one-step process have not been effectively solved.
Through four steps: preparation of esterification liquid, preparation of foaming precursor, foaming and curing, a low-density large-size polyimide foam material is prepared by one-step method. The specific steps include mixing the binary anhydride, polar solvent and fatty alcohol with the binary anhydride, initiator, catalyst and surfactant, and rapidly forming and curing after adding isocyanate and curing agent.
The preparation of low-density large-size polyimide foam material has been realized, and the disadvantages of the original one-step method of high density and large-size cracking are improved. The material has low density, low thermal conductivity, excellent flame retardant properties and small moisture absorption, uniform pore size and stable performance.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer foam materials, in particular to a low-density large-size polyimide foam material and a preparation method thereof. Background Art
[0002] Polyimide (PI) is a type of polymer material with high heat resistance developed in the 1950s. It generally refers to a type of polymer containing an imide ring (-CO-NH-CO-) on the main chain. Polyimide has good electrical insulation, radiation and corrosion resistance, mechanical properties and good processing properties, and is widely used in medicine, shipbuilding, aerospace and other fields. The polyimide material with foam structure not only maintains the excellent heat resistance, flame retardancy, water resistance and radiation resistance of the original resin, but also has outstanding wave transmission characteristics and comprehensive properties such as light weight, low thermal conductivity and good thermal insulation performance. Therefore, it is widely used in the field of military equipment.
[0003] Polyimide foam was first successfully developed by NASA, Langley Research Center and UnitikaAmerica. It was first used as a thermal insulation material for the space shuttle bulkhead. It has important application value in key areas such as thermal insulation, vibration reduction, noise reduction and insulation in high-tech industries such as aerospace, military defense, electronic appliances and new energy vehicles. In addition, foreign polyimide foam materials have been rapidly developed in the United States, Japan, Europe and other countries, such as the Solimide series produced by Inspec Foam in the United States, the TEEK series developed by NASA, the SF series of DuPont, the PEI series of AlcanAirexAG in Switzerland, and the Rohacell series of ROhm in Germany. Polyimide foam is designated as a thermal insulation material for naval ships to improve the environmental adaptability and safety of warships. In addition, it is also used in civilian ships such as luxury cruise ships, speedboats and liquefied natural gas ships.
[0004] At present, there are generally two methods for preparing polyimide foam: a two-step method and a one-step method. The two-step method is to first react aromatic dianhydride or aromatic acid ester with diamine to obtain polyester ammonium salt precursor powder, and then put the polyester ammonium salt precursor powder prepared in advance into a specific mold, and foam it by high-temperature heating to obtain polyimide foam insulation material, but this method has a complicated preparation process, is difficult to operate, has high requirements for the process operation of polyimide foam foaming, and has a low degree of imidization. The one-step method is to react aromatic dianhydride or aromatic acid ester with diamine to foam once through a polycondensation reaction, and directly use the gas generated by the reaction as a foaming agent, and then form polyimide foam through natural curing and high-temperature heating. The polyimide foam preparation process of this method is simple and the cycle is short. It is easy to realize large-scale industrial production of polyimide foam, and can prepare high-density polyimide foam materials with uniform pores and stable performance, but this method is difficult to produce low-density and large-sized foam materials.
[0005] CN106751826A discloses a method of mixing aromatic dianhydride, furfuryl alcohol, fatty alcohol, catalyst, surfactant, modifier and the like with modified black material for foaming to obtain a reinforced and toughened self-curing hard polyimide foam with a density range of 76-113 Kg / m3; tensile strength: 2.56-3.23 MPa; breaking strength: 379-873 N / m; long-term working temperature resistance: 380-450°C. However, the addition of glass microspheres, glass fibers and the like increases the strength and toughness of the product, but also increases the complexity of the production process, making it more difficult to control. CN109810251A discloses a method for preparing a high-performance rigid polyimide heat-insulating sound-absorbing foam, wherein the steps are: dissolving polyisocyanate in a polar solvent under nitrogen protection, adding aromatic anhydride, then adding a surfactant, standing for polymerization and thickening for 5-10 days, and then curing the foam material through microwave and high-temperature oven. The polyimide foam material obtained by the method has a density in the range of 124-261kg / m3; compression strength: 1.2-5.4MPa; glass transition temperature: 330-342℃; 10% decomposition temperature: 532-550℃; average sound absorption coefficient: 0.59-0.65. However, the method has a long free foaming time, a large density of polyimide foam, and generally small production size, and a complex high-temperature curing, resulting in serious energy consumption in the later stage, which has a great impact on industrialization efficiency and cost.
[0006] Therefore, finding a new preparation method that can improve the shortcomings of the original one-step method of high density and large-size cracking is the current key research direction. Summary of the invention
[0007] In order to solve the above technical problems existing in the prior art, the present invention provides a low-density large-size polyimide foam material and a preparation method thereof. Specifically, the present invention is achieved through the following technical solutions:
[0008] A method for preparing a low-density large-size polyimide foam material comprises the following steps:
[0009] (1) Preparation of esterification liquid: dibasic anhydride, polar solvent and fatty alcohol are mixed, and esterification reaction is completed at 50-90° C. to obtain esterification liquid, which is cooled for standby use;
[0010] (2) Preparation of a foaming precursor: The esterification liquid in step (1) is mixed with a dibasic anhydride, an initiator, a catalyst, and a surfactant and stirred until fully mixed to obtain a foaming precursor;
[0011] (3) Foaming: Add isocyanate and curing agent to the foaming precursor in step (2), mix and stir, and then quickly transfer to a mold for molding.
[0012] (4) Curing: The foamed product in step (3) is demoulded and then heated to obtain a polyimide foam material.
[0013] Furthermore, the dibasic anhydride in step (1) is 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 2,3,3',4'-benzophenonetetracarboxylic dianhydride (α-BTDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA), 2,3',4,4'-biphenyltetracarboxylic dianhydride (α-BPDA), 1,2,4,5-pyromellitic dianhydride (PMDA), 3,3',4,4 One or more of '-diphenyl ether tetracarboxylic dianhydride (ODPA), 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride (α-ODPA), 3,3',4,4'-biphenyl sulfone tetracarboxylic dianhydride (DSDA), bisphenol A diphenyl ether dianhydride (BPADA), 3,3',4,4'-diphenyl sulfide tetracarboxylic dianhydride (TDPA) and 3,3',4,4'-triphenyl bis(Q) ether tetracarboxylic dianhydride (HQDA) are mixed in any proportion.
[0014] Furthermore, the polar solvent in step (1) is a mixture of one or more of tetrahydrofuran, 2-chloropyridine, 2,6-dichloropyridine, dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, propylene glycol methyl ether, and dipropylene glycol dimethyl ether.
[0015] Furthermore, the fatty alcohol in step (1) is one or more of methanol, ethanol, ethylene glycol, propanol, isopropanol, n-butanol, n-octanol, and dodecanol mixed in any proportion.
[0016] Furthermore, the mixing ratio of the dibasic anhydride, polar solvent and fatty alcohol in step (1) is the mass ratio: (2-10): (2-10): (1-5).
[0017] Furthermore, the initiator in step (2) is water.
[0018] Furthermore, the catalyst in step (2) is one or more of diethanolamine, triethanolamine, triethylenediamine, dimethylethanolamine, dipropylene glycol, triethylenediamine, organic tin, stannous octoate, dibutyltin diacetate, and dibutyltin dilaurate mixed in any proportion.
[0019] Furthermore, the foam stabilizer in step (2) is one or more of polysiloxane, tetramethyl silicone oil, AK series silicone oil (such as AK8803, AK8805), DC series silicone oil (such as DC19, DC198), silicone polyether copolymer, organosilicon, and silicone mixed in any proportion.
[0020] Furthermore, the mixing ratio of the esterification liquid to the dibasic anhydride, initiator, catalyst and surfactant in step (2) is the mass ratio: (20-100):(30-80):(2-6):(1-3):(3-6).
[0021] Further, the isocyanate in step (3) is one or more of phenylene diisocyanate, p-phenylene diisocyanate, diphenylmethane diisocyanate, polyphenyl polymethylene polyisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, diphenylmethane diisocyanate, toluene diisocyanate, tetramethylxylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, 3,3'-dimethoxy-4,4'-diphenyl diisocyanate, methylcyclohexane diisocyanate, cyclohexyl dimethylene diisocyanate, methyl formate pentamethylene diisocyanate, diphenylmethane-4,4'-diisocyanate, 1,5-naphthalene diisocyanate and dimethylbiphenyl diisocyanate, mixed in any proportion.
[0022] Furthermore, the curing agent in step (3) is one or more of TDI-TMP (toluene diisocyanate-trimethylolpropane), TDI trimer curing agent, HDI trimer curing agent, IPDI trimer, H-4 epoxy curing agent, and ethylenediamine mixed in any proportion.
[0023] Furthermore, in step (4), the heating temperature is 150-300° C. and the heating time is 0.5-6 h.
[0024] The low-density large-size polyimide foam material is prepared by the above preparation method.
[0025] Compared with the prior art, the technical effects created by the present invention are embodied in:
[0026] (1) The preparation process of the present invention is simple, the manufacturing cost is low, and it is easy to industrialize and apply.
[0027] (2) The present invention adopts a one-step method to prepare low-density and large-size low-density polyimide foam, thereby improving the disadvantages of the original one-step method of high density and large-size cracking.
[0028] (3) The low-density large-size polyimide foam material prepared by the present invention has the characteristics of low density, low thermal conductivity, excellent flame retardant performance, and low moisture absorption rate.
[0029] (4) The polyimide foam material prepared by the present invention has uniform pore size and stable performance. Various indicators have been improved to a certain extent compared with other methods, such as the thermal conductivity is reduced to about 0.04W / (m·K), the oxygen index is increased to about 36, the moisture absorption rate is reduced to about 0.3%, and the apparent density is reduced to 10kg / m 3 ~50kg / m 3 In addition, it also has excellent performance in corrosion resistance, smoke resistance, mildew resistance, and sound absorption. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further defined below in conjunction with specific implementation methods, but the scope of protection required is not limited to the description.
[0031] In the present invention, the thermal conductivity of the sample is measured by a DRL-2A thermal conductivity tester under the conditions of 100°C and 50N; the oxygen index is detected by an oxygen index meter BS ISO 4589-2. During the test, the O2 concentration is increased from 22% until the sample cloth burns, and the critical value of the O2 concentration closest to the burning is taken as the limiting oxygen index of the fabric; the apparent density is analyzed by a high-density electronic analytical balance for the apparent density of the polyimide foam material.
[0032] Example 1
[0033] This embodiment provides a method for preparing a low-density large-size polyimide foam material, which specifically comprises the following steps:
[0034] (1) Preparation of esterification liquid: 3,3',4,4'-benzophenonetetracarboxylic dianhydride, N,N-dimethylformamide and methanol were mixed at a ratio of 5:5:1.5, and esterification reaction was completed at 80°C to obtain esterification liquid, which was cooled for later use;
[0035] (2) Preparation of a foaming precursor: The lipidated liquid in step (1) is mixed with 3,3',4,4'-benzophenonetetracarboxylic dianhydride, water, triethanolamine, dipropylene glycol, organotin, tetramethyl silicone oil, and polyethylene glycol in a ratio of 70:55:3:3:4:3 and stirred until fully mixed to obtain a foaming precursor;
[0036] (3) Foaming: Add polyphenyl polymethylene polyisocyanate and curing agent in a ratio of 80:20:10 to the foaming precursor in step (2), and then quickly transfer to a mold for molding;
[0037] (4) Curing: demoulding the foamed product in step (3) and placing it in an oven for heating and curing at a temperature of 220° C. for 4 hours, and cooling to obtain a polyimide foam material;
[0038] Experimental results: thermal conductivity: 0.035, oxygen index: 37, apparent density: 16, mass absorption rate: 0.32.
[0039] Example 2
[0040] This embodiment provides a method for preparing a low-density large-size polyimide foam material, which specifically comprises the following steps:
[0041] (1) Preparation of esterification liquid: 3,3',4,4'-benzophenonetetracarboxylic dianhydride, N,N-dimethylformamide and methanol were mixed in a ratio of 8:6:2.5, and esterification reaction was completed at 90°C to obtain esterification liquid, which was cooled for later use;
[0042] (2) Preparation of a foaming precursor: The lipidated liquid in step (1) is mixed with 3,3',4,4'-benzophenonetetracarboxylic dianhydride, water, triethanolamine, dipropylene glycol, organotin, tetramethyl silicone oil, and polyethylene glycol in a ratio of 70:75:2:3:5:3 and stirred until fully mixed to obtain a foaming precursor;
[0043] (3) Foaming: Add polyphenyl polymethylene polyisocyanate and curing agent in a ratio of 70:18:8 to the foaming precursor in step (2), and then quickly transfer to a mold for molding;
[0044] (4) Curing: demoulding the foamed product in step (3) and placing it in an oven for heating and curing at a temperature of 220° C. for 4 hours, and cooling to obtain a polyimide foam material;
[0045] Experimental results: The large-size surface does not crack, its thermal conductivity is 0.033, oxygen index is 39, apparent density is 30, and mass absorption rate is 0.31.
[0046] Example 3
[0047] This embodiment provides a method for preparing a low-density large-size polyimide foam material, which specifically comprises the following steps:
[0048] (1) Preparation of esterification liquid: 3,3',4,4'-benzophenonetetracarboxylic dianhydride, N,N-dimethylformamide and methanol were mixed in a ratio of 9:7:3, and esterification reaction was completed at 90°C to obtain esterification liquid which was cooled for later use;
[0049] (2) Preparation of a foaming precursor: The lipidated liquid in step (1) is mixed with 3,3',4,4'-benzophenonetetracarboxylic dianhydride, water, triethanolamine, dipropylene glycol, organotin, tetramethyl silicone oil, and polyethylene glycol in a ratio of 100:90:3:3:5:2.5 and stirred until fully mixed to obtain a foaming precursor;
[0050] (3) Foaming: Add polyphenyl polymethylene polyisocyanate and curing agent in a ratio of 90:16:6 to the foaming precursor in step (2), and then quickly transfer to a mold for molding;
[0051] (4) Curing: demoulding the foamed product in step (3) and placing it in an oven for heating and curing at a temperature of 220° C. for 4 hours, and cooling to obtain a polyimide foam material;
[0052] Experimental results: The large-size surface does not crack, its thermal conductivity is 0.035, oxygen index is 40, apparent density is 25, and mass absorption rate is 0.28.
[0053] Example 4
[0054] This embodiment provides a method for preparing a low-density large-size polyimide foam material, which specifically comprises the following steps:
[0055] (1) Preparation of esterification liquid: 3,3',4,4'-benzophenonetetracarboxylic dianhydride, N,N-dimethylformamide and methanol were mixed in a ratio of 9:7:3, and esterification reaction was completed at 90°C to obtain esterification liquid which was cooled for later use;
[0056] (2) Preparation of a foaming precursor: The lipidated liquid in step (1) is mixed with 3,3',4,4'-benzophenonetetracarboxylic dianhydride, water, triethanolamine, dipropylene glycol, organotin, tetramethyl silicone oil, and polyethylene glycol in a ratio of 120:90:3:3:5:1.5 and stirred until fully mixed to obtain a foaming precursor;
[0057] (3) Foaming: Add polyphenyl polymethylene polyisocyanate and curing agent in a ratio of 100:18:7 to the foaming precursor in step (2), stir, and then quickly transfer to a mold for molding;
[0058] (4) Curing: demoulding the foamed product in step (3) and placing it in an oven for heating and curing at a temperature of 220° C. for 4 hours, and cooling to obtain a polyimide foam material;
[0059] Experimental results: The large-size surface does not crack, its thermal conductivity is 0.038, oxygen index is 38, apparent density is 22, and mass absorption rate is 0.26.
[0060] Example 5
[0061] This embodiment provides a method for preparing a low-density large-size polyimide foam material, which specifically comprises the following steps:
[0062] (1) Preparation of esterification liquid: 3,3',4,4'-benzophenonetetracarboxylic dianhydride, N,N-dimethylformamide and methanol were mixed in a ratio of 8:6:2.5, and esterification reaction was completed at 90°C to obtain esterification liquid, which was cooled for later use;
[0063] (2) Preparation of a foaming precursor: The lipidated liquid in step (1) is mixed with 3,3',4,4'-benzophenonetetracarboxylic dianhydride, water, triethanolamine, dipropylene glycol, organotin, tetramethyl silicone oil, and polyethylene glycol in a ratio of 70:75:2:3:3:3 and stirred until fully mixed to obtain a foaming precursor;
[0064] (3) Foaming: Add polyphenyl polymethylene polyisocyanate and curing agent in a ratio of 80:20:12 to the foaming precursor in step (2), stir, and then quickly transfer to a mold for molding;
[0065] (4) Curing: demoulding the foamed product in step (3) and placing it in an oven for heating and curing at a temperature of 220° C. for 4 hours, and cooling to obtain a polyimide foam material;
[0066] Experimental results: The large-size surface does not crack, its thermal conductivity is 0.032, oxygen index is 37, apparent density is 24, and mass absorption rate is 0.31.
[0067] Comparative Example 1:
[0068] This comparative example provides a production method for preparing a large-size polyimide foam material, which specifically comprises the following steps:
[0069] (1) Preparation of esterification liquid: 3,3',4,4'-benzophenonetetracarboxylic dianhydride, N,N-dimethylformamide and methanol were mixed at a ratio of 5:5:1.5, and esterification reaction was completed at 80°C to obtain esterification liquid, which was cooled for later use;
[0070] (2) Preparation of a foaming precursor: The lipidated liquid in step (1) is mixed with 3,3',4,4'-benzophenonetetracarboxylic dianhydride, water, triethanolamine, dipropylene glycol, organotin, tetramethyl silicone oil, and polyethylene glycol in a ratio of 70:55:3:3:4:3 and stirred until fully mixed to obtain a foaming precursor;
[0071] (3) Foaming: adding polyphenyl polymethylene polyisocyanate to the foaming precursor in step (2) in a ratio of 80:20, and then quickly transferring to a mold for molding;
[0072] (4) Curing: demoulding the foamed product in step (3) and placing it in an oven for heating and curing at a temperature of 220° C. for 4 hours, and cooling to obtain a polyimide foam material;
[0073] Experimental results: large-scale surface cracking, thermal conductivity: 0.042, oxygen index: 34, apparent density: 65, mass absorption rate: 0.53
[0074] Comparative Example 2:
[0075] This comparative example provides a production method for preparing a large-size polyimide foam material, which specifically comprises the following steps:
[0076] (1) Preparation of esterification liquid: 3,3',4,4'-benzophenonetetracarboxylic dianhydride, N,N-dimethylformamide and methanol were mixed in a ratio of 8:6:2.5, and esterification reaction was completed at 90°C to obtain esterification liquid, which was cooled for later use;
[0077] (2) Preparation of a foaming precursor: The lipidated liquid in step (1) is mixed with 3,3',4,4'-benzophenonetetracarboxylic dianhydride, water, triethanolamine, dipropylene glycol, organotin, tetramethyl silicone oil, and polyethylene glycol in a ratio of 70:75:2:3:5:3 and stirred until fully mixed to obtain a foaming precursor;
[0078] (3) Foaming: adding polyphenyl polymethylene polyisocyanate to the foaming precursor in step (2) at a ratio of 70:18, and then quickly transferring to a mold for molding;
[0079] (4) Curing: demoulding the foamed product in step (3) and placing it in an oven for heating and curing at a temperature of 220° C. for 4 hours, and cooling to obtain a polyimide foam material;
[0080] Experimental results: There are cracks on the large-size surface, its thermal conductivity: 0.049, oxygen index: 32, apparent density: 71, mass absorption rate: 0.6 Comparative Example 3:
[0081] This comparative example provides a production method for preparing a large-size polyimide foam material, which specifically comprises the following steps:
[0082] (1) Preparation of esterification liquid: 3,3',4,4'-benzophenonetetracarboxylic dianhydride, N,N-dimethylformamide and methanol were mixed in a ratio of 9:7:3, and esterification reaction was completed at 90°C to obtain esterification liquid which was cooled for later use;
[0083] (2) Preparation of a foaming precursor: The lipidated liquid in step (1) is mixed with 3,3',4,4'-benzophenonetetracarboxylic dianhydride, water, triethanolamine, dipropylene glycol, organotin, tetramethyl silicone oil, and polyethylene glycol in a ratio of 100:90:3:3:5:2.5 and stirred until fully mixed to obtain a foaming precursor;
[0084] (3) Foaming: adding polyphenyl polymethylene polyisocyanate to the foaming precursor in step (2) and stirring at a ratio of 90:16, and then quickly transferring to a mold for molding;
[0085] (4) Curing: demoulding the foamed product in step (3) and placing it in an oven for heating and curing at a temperature of 220° C. for 4 hours, and cooling to obtain a polyimide foam material;
[0086] Experimental results: large-size surface cracking, thermal conductivity: 0.046, oxygen index: 33, apparent density: 68, mass absorption rate: 0.6 Comparative Example 4:
[0087] This comparative example provides a production method for preparing a large-size polyimide foam material, which specifically comprises the following steps:
[0088] (1) Preparation of esterification liquid: 3,3',4,4'-benzophenonetetracarboxylic dianhydride, N,N-dimethylformamide and methanol were mixed in a ratio of 9:7:3, and esterification reaction was completed at 90°C to obtain esterification liquid which was cooled for later use;
[0089] (2) Preparation of a foaming precursor: The lipidated liquid in step (1) is mixed with 3,3',4,4'-benzophenonetetracarboxylic dianhydride, water, triethanolamine, dipropylene glycol, organotin, tetramethyl silicone oil, and polyethylene glycol in a ratio of 120:90:3:3:5:1.5 and stirred until fully mixed to obtain a foaming precursor;
[0090] (3) Foaming: adding polyphenyl polymethylene polyisocyanate to the foaming precursor in step (2) in a ratio of 100:18, and then quickly transferring to a mold for molding;
[0091] (4) Curing: demoulding the foamed product in step (3) and placing it in an oven for heating and curing at a temperature of 220° C. for 4 hours, and cooling to obtain a polyimide foam material;
[0092] Experimental results: There are cracks on the large-size surface, its thermal conductivity: 0.045, oxygen index: 30, apparent density: 56, mass absorption rate: 0.7 Comparative Example 5:
[0093] This comparative example provides a production method for preparing a large-size polyimide foam material, which specifically comprises the following steps:
[0094] (1) Preparation of esterification liquid: 3,3',4,4'-benzophenonetetracarboxylic dianhydride, N,N-dimethylformamide and methanol were mixed in a ratio of 8:6:2.5, and esterification reaction was completed at 90°C to obtain esterification liquid, which was cooled for later use;
[0095] (2) Preparation of a foaming precursor: The lipidated liquid in step (1) is mixed with 3,3',4,4'-benzophenonetetracarboxylic dianhydride, water, triethanolamine, dipropylene glycol, organotin, tetramethyl silicone oil, and polyethylene glycol in a ratio of 70:75:2:3:3:3 and stirred until fully mixed to obtain a foaming precursor;
[0096] (3) Foaming: adding polyphenyl polymethylene polyisocyanate to the foaming precursor in step (2) in a ratio of 80:20, and then quickly transferring to a mold for molding;
[0097] (4) Curing: demoulding the foamed product in step (3) and placing it in an oven for heating and curing at a temperature of 220° C. for 4 hours, and cooling to obtain a polyimide foam material;
[0098] Experimental results: large-scale surface cracking, thermal conductivity: 0.047, oxygen index: 31, apparent density: 61, mass absorption rate: 0.5 Finally, it should be pointed out that the above embodiments are only representative examples of the present invention. Obviously, the technical solution of the present invention is not limited to the above embodiments, and there can be many variations. All variations that can be directly derived or associated with the content disclosed by ordinary technicians in this field should be considered as the protection scope of the present invention.
Claims
1. A method for preparing a low-density large-size polyimide foam material, characterized in that: The steps include: (1) Preparation of esterification liquid: dibasic anhydride, polar solvent and fatty alcohol are mixed, and esterification reaction is completed at 50-90° C. to obtain esterification liquid, which is cooled for standby use; (2) Preparation of a foaming precursor: The esterification liquid in step (1) is mixed with a dibasic anhydride, an initiator, a catalyst, and a surfactant and stirred until fully mixed to obtain a foaming precursor; (3) Foaming: Add isocyanate and curing agent to the foaming precursor in step (2), mix and stir, and then quickly transfer to a mold for molding. (4) Curing: The foamed product in step (3) is demoulded and then heated to obtain a polyimide foam material.
2. The preparation method according to claim 1, characterized in that: The dibasic anhydride in step (1) is 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 2,3,3',4'-benzophenonetetracarboxylic dianhydride (α-BTDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA), 2,3',4,4'-biphenyltetracarboxylic dianhydride (α-BPDA), 1,2,4,5-pyromellitic dianhydride (PMDA), 3,3',4,4'-diphenyltetracarboxylic dianhydride (s-BPDA), 2,3',4,4'-di ...1,2,4,4'-diphenyltetracarboxylic dianhydride (s-BPDA), 1,2,4,5-diphenyltetracarboxylic dianhydride (PMDA), 1,2,4,4'-diphenyltetracarboxylic dianhydride (s-BPDA), 1,2,4,5-diphenyltetracarboxylic dianhydride (s-BPDA), 1,2,4,4'-diphenyltetracarboxylic dianhydride (s-BPDA), 1,2,4,4'-diphenyltetracarboxylic dianhydride (s-BPDA), 1,2,4,5-diphenyltetracarboxylic dianhydride (s-BPDA), 1,2,4,4'-diphenyl One or more of phenyl ether tetracarboxylic dianhydride (ODPA), 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride (α-ODPA), 3,3',4,4'-biphenyl sulfone tetracarboxylic dianhydride (DSDA), bisphenol A diphenyl ether dianhydride (BPADA), 3,3',4,4'-diphenyl sulfide tetracarboxylic dianhydride (TDPA) and 3,3',4,4'-triphenyl bis(QQDA) tetracarboxylic dianhydride (HQDA) are mixed in any proportion.
3. The preparation method according to claim 1, characterized in that: The polar solvent in step (1) is a mixture of one or more of tetrahydrofuran, 2-chloropyridine, 2,6-dichloropyridine, dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, propylene glycol methyl ether, and dipropylene glycol dimethyl ether.
4. The preparation method according to claim 1, characterized in that: The fatty alcohol in step (1) is one or more of methanol, ethanol, ethylene glycol, propanol, isopropanol, n-butanol, n-octanol and dodecanol mixed in any proportion.
5. The preparation method according to claim 1, characterized in that: The mixing ratio of the dibasic anhydride, polar solvent and fatty alcohol in the step (1) is (2-10):(2-10):(1-5) by mass.
6. The preparation method according to claim 1, characterized in that: The initiator in step (2) is water.
7. The preparation method according to claim 1, characterized in that: The catalyst in step (2) is one or more of diethanolamine, triethanolamine, triethylenediamine, dimethylethanolamine, dipropylene glycol, triethylenediamine, organic tin, stannous octoate, dibutyltin diacetate, and dibutyltin dilaurate, mixed in any proportion.
8. The preparation method according to claim 1, characterized in that: The foam stabilizer in step (2) is one or more of polysiloxane, tetramethyl silicone oil, AK series silicone oil, DC series silicone oil, silicone polyether copolymer, organosilicon, and silicone mixed in any proportion.
9. The preparation method according to claim 1, characterized in that: The mixing ratio of the esterification liquid to the dibasic anhydride, initiator, catalyst and surfactant in the step (2) is the mass ratio: (20-100):(30-80):(2-6):(1-3):(3-6).
10. The preparation method according to claim 1, characterized in that: The isocyanate in the step (3) is one or more of phenylene diisocyanate, p-phenylene diisocyanate, diphenylmethane diisocyanate, polyphenyl polymethylene polyisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, diphenylmethane diisocyanate, toluene diisocyanate, tetramethylxylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, 3,3'-dimethoxy-4,4'-diphenyl diisocyanate, methylcyclohexane diisocyanate, cyclohexyl dimethylene diisocyanate, methyl formate pentamethylene diisocyanate, diphenylmethane-4,4'-diisocyanate, 1,5-naphthalene diisocyanate and dimethylbiphenyl diisocyanate, mixed in any proportion.
11. The preparation method according to claim 1, characterized in that: The curing agent in step (3) is one or more of TDI-TMP, TDI trimer curing agent, HDI trimer curing agent, IPDI trimer, H-4 epoxy curing agent, and ethylenediamine mixed in any proportion.
12. The preparation method according to claim 1, characterized in that: In the step (4), the heating temperature is 150-300° C. and the heating time is 0.5-6 h.
13. A low-density large-size polyimide foam material prepared by the preparation method according to any one of claims 1 to 12.
Citation Information
Patent Citations
Reinforcing and toughening self-setting hard polyimide foam and preparation method thereof
CN106751826A
Preparation method of high-performance hard polyimide heat insulation sound absorption foam
CN109810251A